2013
DOI: 10.1002/eqe.2288
|View full text |Cite
|
Sign up to set email alerts
|

Residual drift demands in moment‐resisting steel frames subjected to narrow‐band earthquake ground motions

Abstract: SUMMARY This paper presents the main results of the evaluation of residual inter‐story drift demands in typical moment‐resisting steel buildings designed accordingly to the Mexican design practice when subjected to narrow‐band earthquake ground motions. Analytical 2D‐framed models representative of the study‐case buildings were subjected to a set of 30 narrow‐band earthquake ground motions recorded on stations placed in soft‐soil sites of Mexico City, where most significant structural damage was found in build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…For example, median RIDR demands triggered by low intensity aftershocks are larger than those induced by high-intensity aftershocks in the lower stories of the 12-story building. As discussed in [21], this is a result of the large record-to-record variability inherent in the estimation of residual drift demands.…”
Section: Response Under Seismic Sequencesmentioning
confidence: 97%
“…For example, median RIDR demands triggered by low intensity aftershocks are larger than those induced by high-intensity aftershocks in the lower stories of the 12-story building. As discussed in [21], this is a result of the large record-to-record variability inherent in the estimation of residual drift demands.…”
Section: Response Under Seismic Sequencesmentioning
confidence: 97%
“…Due to soft story mechanism, plastic hinges are mainly distributed at the column ends in one story, rather than beam ends, which usually results in limited ductility and poor energy dissipation. Large residual drift and concentrated damage severely hamper the reparability and fast resilience of RC frame structures after earthquakes …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the residual drift in buildings greater than 0.5 % might cause a complete loss of structures from an economic perspective. Another recent study [4] reported that the residual inter-story drift in traditional moment resisting frames greater than 0.5 % may cause human discomfort when structure subjected to long-duration earthquake motions. Erochko et al [5] investigated the residual drift response of special momentresisting frames (SMRFs) and buckling-restrained braced frames (BRBFs) and reported that both types of building systems reveal extensive residual drifts; 0.5-1.2 % for SMRFs and 0.8-1.8 % for BRBFs.…”
mentioning
confidence: 98%